Islamo-English: a variety of English for the Ummah - Mohamed Ali, Haja Mohideen (KD Publications, India, 2014)
Islamo-English is a term preferred by the present researcher to refer to Islam-related and Muslim related content through the medium of English. Much Islamic knowledge is expressed through English, not only in academic and professional publications, but also in popular reading materials, both online and in print. Besides this there is creative writing and lyrics which are conveyed through Islamo-English. The aim of this paper is to study Islam-related vocabulary in Arabic mainly and other Muslim-majority languages.